PEMIKIRIAN KH.HASYIM ASY’ARI TENTANG PENDIDIKAN AKHLAK DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER DI INDONESIA (Telaah Kitab Âdâb al-‘Âlim wa al-Muta’allim) - Erry Fujo Dwilaksono; M. Miftahul Ulum; Nuraini Nuraini (TARBAWI:Journal on Islamic Education, 2020)
The moral education in the Book of Âdâb al-'âlim wa al-Muta'allim is in line with the government program that pays special attention to character education to make researchers interested in studying the book comprehensively. The purpose of this study is to describe the concept of KH. Hasyim Asy'ari related to education, the concept of character education in Indonesia and the relevance of the concept of moral education thought. Hasyim Asy'ari with character education in Indonesia. The type of research used is literature research or in the term Ain is called a library research with a descriptive method, with the data collection tools documentation and data sources consist of primary data sources, namely from the book Âdâb al-' Âlim wa al-Muta'allim by KH. Hasas'ari. The results of the study and discussion concluded that: the concept of KH thought. Hasyim Asy'ari about moral education is to direct someone to more religious values, the concept of character education in Indonesia is reflected in the program PPK, and the conclusion of Irian moral education. Hasyim Asy'ari has relevance to the character education in Indonesia.